1956
DOI: 10.1111/j.1651-2227.1956.tb17682.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Findings Characteristic of Rickets in Foetuses and Young Infants

Abstract: Summary The oste‐ochondral junctions of the first or second and the sixth or seventh rib have been removed from foetuses and infants in 527 consecutive autopsies and examined histologically for the occurrence of changes typical of rickets. The distribution of the series following birth weight and age appears from Table 1. The following histological changes have been searched for: A, Broadening and gross irregularity of the osteochondral junction; B, irregular arrangement of the cartilage cells at the ossificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…FOLLIS (1952) observed only two cases of slight rickets among 360 infants dying within the first two weeks of life, and none among 162 still-born infants. On the other hand, VON SYDOW et al (1956) reported a high incidence of rickets at autopsy of both foetuses and infants, though the percentage was lowest in full-term still-born infants. In our small series, the occurrence of rickets in 4 infants dying within the first 25 days of life is of interest.…”
Section: Discussionmentioning
confidence: 91%
“…FOLLIS (1952) observed only two cases of slight rickets among 360 infants dying within the first two weeks of life, and none among 162 still-born infants. On the other hand, VON SYDOW et al (1956) reported a high incidence of rickets at autopsy of both foetuses and infants, though the percentage was lowest in full-term still-born infants. In our small series, the occurrence of rickets in 4 infants dying within the first 25 days of life is of interest.…”
Section: Discussionmentioning
confidence: 91%
“…The histology of vitamin D-deficiency rickets has been described in the pathology literature [15][16][17][18][19], and is characterized within long bones by widening of the growth plate accompanied by architectural disarray. This is a result of a failure of the chondrocytes within the zone of hypertrophy to undergo apoptosis, and leads to the accumulation of hypertrophic cartilage.…”
Section: Discussionmentioning
confidence: 98%